ANALISIS KESALAHAN BERBAHASA DALAM TATARAN SEMANTIK PADA POSTINGAN AKUN INSTAGRAM @demauinsurakarta - Refliani Faradilla Barkah (Jurnal Bahasa Lingua Scientia, 2023)
This research is motivated by the use of the Indonesian language where there are still many errors found, especially at the semantic level. The purpose of this study is to find out language errors at the semantic level contained in the @demauinsurakarta account. This study uses a qualitative descriptive method approach. The data source in this study is the account caption @demauinsurakarta. This study uses data analysis methods in the form of references from the Kamus Besar Bahasa Indonesia (KBBI) and Pedoman Umum Ejaan Bahasa Indonesia (PUEBI). The results of this study found semantic level errors in the field of hypercorrection found 7 errors, pleonasm found 8 errors, inappropriate word choice or diction found 3 errors and word selection which resulted in ambiguity meaning found 3 errors.